A comprehensive characterization biotransformation of chlorinated paraffin by human and carp liver microsomes via liquid chromatography-high-resolution mass spectrometry and screening algorithm - Liujun Chen; Caiming Tang; Zhiqiang Yu; Yanhong Zeng; Bixian Mai; Xiaojun Luo (Environment International)
The chlorinated paraffin (CP) monomer 1,2,5,6,9,10-Hexachlorodecane (CP-4) was subjected to in vitro biotransformation using human and carp liver microsomes. Five types of CP-4 metabolites (OH–, keto-, enol-, aldehyde- and carboxy-CP-4) were identified in human liver microsomer while only mono-OH-CP-4 was found in the carp liver microsomes. Kinetic studies revealed that the formation of mono-, di-, tri-hydroxylated CP-4, keto-, enol-, and aldehyde-CP-4 in human liver microsomes was best described by substrate inhibition models, whereas the formation of carboxylated CP-4 metabolites best fit the Michaelis–Menten model. Notably, keto-CP-4, enol-CP-4 and aldehyde-CP-4 were the predominant metabolites. The estimated Vmax values for these metabolites were significantly higher in the human liver microsomes than in the carp liver microsomes. The intrinsic hepatic clearance (CLint) of CP-4 was higher in humans than in carp, indicating species-specific differences in its metabolism. This study also highlighted potential toxicity concerns, with computational predictions showing varying degrees of acute oral toxicity for CP-4 and its metabolites. These findings indicate significant species-specific differences in the biotransformation of CP-4, emphasizing the potential health and environmental risks associated with chlorinated paraffins and their metabolites, and underscore the need for further research to address these concerns.